SUATU KAJIAN AWAL TERHADAP TINGKAT PELECEHAN SEKSUAL DI ACEH - Syaiful Bahri; . Fajriani (Majelis Pendidikan Daerah (MPD) Aceh dan Universitas Syiah Kuala, 2015)
This is a preliminary study about the level of sexual harassment in Aceh, this study aims at describing the profile of victims of sexual abuse, sexual harassment diversity of forms of behavior that is natural, the environment in which the abuse and the causes that trigger sexual abuse so that they can be the basis of subsequent policy research in order to formulate various sexual harassment prevention strategies. A a survey is conducted by using quantitative and qualitative descriptive approaches with sample selection refers to the consideration of the sampling area. Eight regencies/cities, namely Subulussalam/Singkil district and South Aceh's western coastal areas, Aceh Besar, Pidie, North Aceh and East Aceh's eastern coastal region and the Southeast Aceh Regency and Central Aceh for the central region. Data obtained through documentation and interviews were analyzed using the descriptive statistics (percentage tabulations, graphs and charts) as well as a comparative analysis of narrative logic. The results showed that, majority of sexual abuse victims are children and young women aged under 18 years old, still a student, the socioeconomic status of the family was in the middle to lower. While the perpetrators including men who come from different backgrounds in terms of ages, education, occupation, socioeconomic status, and place of residence. Forms of sexual abuse cases were rape and sexual abuse, in addition to the act of sodomy in a minority of cases. The cause of sexual harassment is a lack of parental supervision of children, the declining morality of the offender and economic factors. Psychological impact experienced by victims of sexual harassment is that they tend to be aloof, socially isolated people, expelled from school, self-blame, and prolonged trauma. The study recommends that forms of prevention and mitigation of sexual abuse should be implemented.